2019
DOI: 10.1002/ejlt.201900132
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Form of Dietary Selenium Affects the Fatty Acids Profile and Oxidative Stability of Muscles of Broilers Supplemented with Lycopene and Oils

Abstract: The aim of this study is to determine the effects of the addition of different chemical forms of selenium (Se)-selenate (SeVI) or selenized yeast (SeY) to chickens' diet containing equal amounts of fish (FO) and sunflower oils and lycopene (Lyc) on fatty acids (FA) profile and peroxidation yield in thigh muscles of chickens. FA profile is analyzed by gas chromatography coupled with mass spectrometry while content of malondialdehyde is determined by ultra-fast liquid chromatography (UPLC) with photodiode detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…It is noteworthy to indicate that Se levels in cardiac tissue of the CLAplus group demonstrated a significant negative dependence with MDA content. This confirms antioxidant properties of Se and suggests antioxidant properties of CLA isomers [ 32 ] as well as an interaction between CLA and Se content in tissues, which we observed previously [ 44 ]. However positive correlations among Se and AI and TI reveal the strong need for further research concerning CLA and Se interactions as well as their health implication in both physiological and pathological conditions.…”
Section: Discussionsupporting
confidence: 90%
“…It is noteworthy to indicate that Se levels in cardiac tissue of the CLAplus group demonstrated a significant negative dependence with MDA content. This confirms antioxidant properties of Se and suggests antioxidant properties of CLA isomers [ 32 ] as well as an interaction between CLA and Se content in tissues, which we observed previously [ 44 ]. However positive correlations among Se and AI and TI reveal the strong need for further research concerning CLA and Se interactions as well as their health implication in both physiological and pathological conditions.…”
Section: Discussionsupporting
confidence: 90%
“…On the contrary, So et al (2019) stated that apparent digestibility, nutrients intake, DM, crude protein and organic matter digestibility were increased in animals fed rations containing tomato pomace. Diets containing lycopene such as tomatoes can improve the nutritive value of animal products and human health (Czauderna et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Koutsos, Clifford, Calvert, and Klasing (2003) observed that plasma and liver carotenoids were reduced in immune challenge chicken, while higher concentration of carotenoids in the bursa and thymus was noted. The dietary addition of lycopene pigment (12 mg/kg) along with other chemical compounds such as selenium and fish oil, enhance production performance, nutritional value and oxidative stability of broiler meat (Czauderna, Białek, Białek, Śliwiński, & Brzóska, 2019). In another study evaluated the impact of lycopene supplementation on production performance, biochemical parameters and antioxidant capacity, it was noted that 40 mg/kg dietary lycopene significantly improved chick body weight, liver total antioxidant capacity and reduce liver malondialdehyde (MDA) in broiler chicks (Sun et al., 2015).…”
Section: Health Benefits Of Carotenoids For Poultrymentioning
confidence: 99%